2013
DOI: 10.4067/s0718-95162013005000041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fulvic acid on the phosphorus availability in acid soil

Abstract: The incubation experiment was conducted to evaluate the influence of fulvic acid (FA) on phosphorus (P) movement and transformation in acid soil. FA at the rate of 0, 0.1, 0.2, 0.3 g and in combination with 0.19 g KH 2 PO 4 was sprinkled uniformly on the surface of the filter paper on the soil cylinder for 21 days incubation, respectively. The result showed that the pH of soil treated with FA increased from the original value of 5.83 to the highest value of 6.27 in the surface soil layer after 21 days incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 23 publications
5
40
1
1
Order By: Relevance
“…The acidity of most Brazilian soils, especially in subsurface horizons (B), limits establishing and developing production systems for a substantial number of crops (Caires et al, 2008). This may be due to toxic Al and Mn concentrations (Bojórquez-Quintal et al, 2017;Tandzi et al, 2018), low exchangeable Ca 2+ and Mg 2+ levels, and low sum of bases (S), base saturation (V%), and P, unfavorable soil properties for growing most crops (Yang et al, 2013;Maluf et al, 2018). However, some soils contain aluminum levels extracted with 1 mol L -1 KCl (Al-KCl) solution exceeding 10 cmol c kg -1 , where plants exhibit no signs of Al 3+ toxicity and obtain satisfactory yields.…”
Section: Introductionmentioning
confidence: 99%
“…The acidity of most Brazilian soils, especially in subsurface horizons (B), limits establishing and developing production systems for a substantial number of crops (Caires et al, 2008). This may be due to toxic Al and Mn concentrations (Bojórquez-Quintal et al, 2017;Tandzi et al, 2018), low exchangeable Ca 2+ and Mg 2+ levels, and low sum of bases (S), base saturation (V%), and P, unfavorable soil properties for growing most crops (Yang et al, 2013;Maluf et al, 2018). However, some soils contain aluminum levels extracted with 1 mol L -1 KCl (Al-KCl) solution exceeding 10 cmol c kg -1 , where plants exhibit no signs of Al 3+ toxicity and obtain satisfactory yields.…”
Section: Introductionmentioning
confidence: 99%
“…In general, temperate cereals, such as wheat and barley have higher root length and specific root length than legumes under different water regimens (Gregory and Eastham 1996). However, legumes could compensate for their lower root length through a higher P uptake per unit of root length, since legumes have shown higher organic exudation than wheat (Nuruzzaman et al, 2006;Pearse et al, 2006); this increases P mobility and uptake (Hinsinger, 2001;Yang et al, 2013). Nevertheless, to the best of our knowledge, there are no studies comparing wheat and pea's P uptake and root traits under the same field experiments, which would allow us to elucidate possible differences between these crops in relation to this subject.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium spp (Yigit and Dikilitaş, 2008), promote plant growth and increase marketable yield in tomato production (Suh et al, 2014), improved plant growth and yield quantity and quality as well as controlling powdery and downy mildews of cucumber plants and enhanced the activity of soil microorganism (Kamel et al, 2014), enhanced effectively the physiological activities and yield production of tomato plants, as antitranspirants via conserving soil water and thereby reduce the applied water by 25% of irrigation water (Aggag et al, 2015), improve the white rot disease resistance of grape, the quality of berry fruit and more absorption of calcium by grape (Huanpu et al, 2004), enhanced potassium levels in leaves of tobacco (Priya et al, 2014). Also Yang et al (2013) have demonstrated that fulvic acid is optimum choice for the improvement of P availability and soil physicochemical conditions. Xudan (1987) has demonstrated that spraying with fulvic acid can decrease the water stress or the stress imposed by hot, dry winds during ear development and it can increase the grain yield by 7.3-18.0% (Xudan, 1987).…”
Section: Introductionmentioning
confidence: 99%